Lattice strain evolution during creep in single-crystal superalloys - Coakley, J; Reed, R; Warwick, J; Rahman, K; Dye, D (2012)
In situ neutron diffraction studies are carried out to characterize the micromechanical deformation occurring during tensile creep of a typical single-crystal nickel-based superalloy, CMSX-4. The loading responses of the matrix γ phase and the precipitate γ′ are distinct. Moreover, the behaviour in the tertiary creep regime (in which the γ′ phase remains intact) is qualitatively different from that in the primary creep regime (when γ′ is sheared). In tertiary creep, initial deformation of the matrix leads to a release of misfit between the phases in the (1 0 0), resulting in elastic compression of the γ in the loading direction. The load state then remains fairly constant during creep. During the initial stages of primary creep, elastic compression of the γ phase is observed until at around 2-4% creep strain this compression stabilizes as the (1 0 0) misfit is released. This is the point at which γ′ shearing is thought to begin. Subsequently, the load in the γ increases by around 200 MPa until a maximum is reached at around 8% creep strain. This load is then suddenly released, which may be due to the release of back-stress. © 2011 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.